Monopolistic Competition and Different Wage Setting Systems. (February 2014) - García, José Ramón; Sorolla, Valeri
Abstract In this paper, we present a disequilibrium unemployment model without labor market frictions and monopolistic competition in the goods market within an infinite horizon model of growth. We consider different wage setting systems and compare wages, the unemployment rate, and income per capita in the long‐run at firm, sector, and national (centralized) levels. The aim of this paper is to determine under which conditions, the inverted‐U hypothesis between unemployment and the degree of centralization of wage bargaining, reported by Calmfors and Driffill [Economic Policy, 6, 14–61, 1988], is confirmed. Our analysis shows that a high degree of market power normally produces the inverted‐U shape for unemployment. Moreover, we also illustrate that this inverted‐U shape can be reversed when the ability of trade unions to internalize the provision of social services is great enough at sector level.